The Strategies of the Development of the Lexical knowledge for the Moroccan Students: Elementary Levels as a Model: Language Acquisition - Hammou, Mohammed (Al-Ḍād Journal, 2022)
This research seeks to reveal the ways in which the Moroccan learner determines the meanings of vocabulary, in addition to determining the extent of the development of his lexical knowledge from the first level to the fourth level. Through a lexical knowledge test, a sample of 80 male and female students was divided into the following primary levels: the first level, the second level, the third level, and the fourth level. The test is based on a number of vocabulary taken from the reading texts found in government textbooks that are used in teaching Arabic at the elementary levels in Morocco. Keywords: lexical knowledge, Moroccan students, elementary levels